2019
DOI: 10.1080/21870764.2019.1701221
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity-controlled Zn-doped MgO/Mg(OH)2 micro-structures for high-efficiency thermo-dynamic heat energy storage

Abstract: Zn-doped MgO/Mg(OH) 2 was used to increase thermal energy storage efficiency. Among general bulk materials, the thermal conductivity of those materials used for high-efficiency thermal energy storage should be high. In micro (or nano) structures, however, the lower the thermal conductivity, the heat can be more easily concentrated on the surface, enabling a thermodynamic reaction to store heat energy to be easily induced. Zn-doped MgO limits the vibration of the lattice and ultimately lowers the thermal conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Although the two devices demonstrate similar temperature trends as a function of laser power, Cu/Cs 3 Bi 2 I 9 /ITO displayed a higher temperature than Cu/BiI 3 /ITO under the illumination of the same power of irradiation. The lower thermal conductivity of Cs 3 Bi 2 I 9 compared to BiI 3 (Figure b,c) induces higher photoresponse at higher temperatures inside the Cs 3 Bi 2 I 9 thin film due to the more accumulated heat from Cu/Cs 3 Bi 2 I 9 /ITO …”
Section: Resultsmentioning
confidence: 99%
“…Although the two devices demonstrate similar temperature trends as a function of laser power, Cu/Cs 3 Bi 2 I 9 /ITO displayed a higher temperature than Cu/BiI 3 /ITO under the illumination of the same power of irradiation. The lower thermal conductivity of Cs 3 Bi 2 I 9 compared to BiI 3 (Figure b,c) induces higher photoresponse at higher temperatures inside the Cs 3 Bi 2 I 9 thin film due to the more accumulated heat from Cu/Cs 3 Bi 2 I 9 /ITO …”
Section: Resultsmentioning
confidence: 99%
“…The gradual change of the temperature setting value during peak hours is also not conducive to shutting down the electric heat pump load quickly. From the perspective of energy consumption, it is found that the peak-shaving strategy has the lowest energy consumption because it cuts the load and reduces the total energy consumption [10]. The energy consumption of the pre-heating load before and after the improvement is greater than the peak shaving strategy and the constant set value strategy.…”
Section: Duration Of Average Temperature Violationmentioning
confidence: 99%
“…Due to the low thermal conductivity of polymer packaging materials, the thermal conductivity of the polymer is usually improved by adding high thermal conductivity fillers. The filler-filled thermal conductive polymer materials are mainly prepared by adding high thermally conductive metal materials (such as copper powder, , silver powder, metal sheet, and wire ), carbon materials (such as carbon fiber, graphene, graphite, carbon nanotube, and carbon black ) or high thermal conductive inorganic fillers (such as aluminum nitride, , boron nitride, silicon nitride, , silicon carbide, magnesium oxide, , silicon oxide, alumina, barium titanate, and zinc oxide) and other high thermal conductivity fillers (such as MXene ). Filler-filled thermal conductive polymer composites have the advantages of a simple preparation method, low cost, suitable types of polymers, and fillers.…”
Section: Introductionmentioning
confidence: 99%